La funcionalidad familiar y su relación con las alteraciones psico afectivas en los adolescentes de Bachillerato de la zona 7 de Ecuador 2016. - Juca Aulestia, César Fabián (2017)
Adolescence is a time of change that predisposes young people to vulnerability and emotional instability; being within the family where its perpetuation occurs. The study of psycho-affective alterations in adolescents is important in our society due to their high prevalence, since they are largely tolerated by the population as if they were superficial somatic complaints or owing to health teams not having the capability to identify this type of disorder. Therefore, their study is pertinent given the social relevance and the application in clinical practice of primary health care that is provided to detect these alterations early. This research aimed to establish the relationship between family functionality and psycho-affective alterations in high school adolescents from the Provinces of El Oro, Loja and Zamora Chinchipe by comparing the obtained results, according to their sex, through a non-experimental quantitative study. This study administered a socioeconomic level stratification survey pertaining to the National Institute of Statistics and Censuses (INEC), a FFSIL Family Performance Test and an Achenbach and Edelbrock (YSR) child behavior checklist to 960 high school students aged 15 and 19 years old. The results indicate that adolescents from dysfunctional families are 1.8 times more likely to present psycho-affective alterations than those from functional families; these alterations depend on the sex of the adolescent, being higher in females X2=26, 598, p: 0.000 and with Cramer's V: 0.16. This study shows the need to apply the instruments of psycho-affective evaluation to adolescents during the family medical consultation to determine psycho-affective pathologies and in this way, to allow early prevention. Keywords: Emotions, Adolescents, family, behaviors, internalizing, externalizing